Generalized periodic solutions of quasilinear equations - Khoma, N. H.; Khoma, L. G. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We study a boundary-value periodic problem for the quasilinear equationu ff −u xx =F[u,u f u x ],u(0,t) =u (π,t),u (x, t + π/q) =u(x, t), 0 ≤x ≤π,t ∈ ℝ,q ∈ ℕ. We establish conditions under which the theorem on the uniqueness of a smooth solution is true.